The Responsibility To Protect As A New Approach To The Legality Of The Use Of Force For Humanitarian Purposes (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The plea to prevent or stop human rights violations and save the civilian population from an imminent danger, for a state or group of states to intervene in the internal affairs of another state without its consent, is not new. The first roots of this idea go back several centuries, and we have witnessed in all times attempts to legitimize interventions in the internal affairs of countries in the name of protecting the rights of minorities, protecting subjects, protecting the population and human rights, protecting civilians, and for this purpose, the concepts of "just war" were invented, respectively, “Intervention in the name of humanity”, “the right to intervene, the duty to intervene,” the last of which is the principle of the “responsibility to protect,” which aims to protect civilians from the most international crimes that violate human rights without prejudice to the sovereignty of states. The naming of these concepts are the variable. Almost the same to the point of congruence; Because it revolved around the same goal, which is to moralize and, if possible, legal, military interventions in other countries.